COUNTER-NARRATIVE DAKWAH DIGITAL: MENANGKAL ISLAMOFOBIA MELALUI KONTEN POSITIF (Program Studi Komunikasi dan Penyiaran Islam, 2024)
Islamophobia, as a form of negative prejudice against Islam and Muslims, has become increasingly prominent in the digital age. Negative narratives about Islam are widely disseminated through social media and digital platforms, fuelling stereotypes, discrimination, and even symbolic violence. In this context, digital da'wah plays a strategic role as a counter-narrative to present a peaceful, tolerant, and humanistic image of Islam. This article analyses how digital da'wah content can be constructed to effectively counter Islamophobia through a positive narrative approach. Using literature review and content analysis methods, this paper argues that inclusive da'wah content, rooted in universal values and communicated through appropriate strategies, can mitigate negative sentiments while strengthening Islam's image as a religion of mercy for all creation in the virtual space.